Understanding mechanisms of changes in lead bioaccessibility in amended alkaline soils through integration of multiple techniques and evaluating methods for house dust collection and assessing dust lead bioaccessibility - Wekumbure Gedara, Chandima Wekumbura (Kansas State University, 2024)
Soil contamination by trace elements, particularly lead (Pb), presents a global concern, especially affecting young children who are highly susceptible to Pb toxicity through inadvertent ingestion of Pb-contaminated soils and dust. First two studies aimed to assess the efficacy of organic and inorganic soil amendments in reducing bioaccessible Pb concentrations in four soils collected from arid to semi-arid regions with prevailing soil alkalinity. This research also sought to examine the impact of these amendments on changes in Pb speciation and associated in vitro Pb bioaccessibility across four soils with varying Pb concentrations. One soil sample (EP4) was collected from a near ASARCO smelter with a high total Pb concentration (~3000 mg kg⁻¹) and three other soil samples (EP1, EP2, EP3) were collected from residential areas of El Paso, Texas, exhibiting Pb concentrations mild to moderate (750 to 150 mg kg⁻¹). These soils were treated with two organic (Class A, Fe-rich biosolids and compost) at two rates (5 and 10%) and two inorganic P fertilizers (triple superphosphate, TSP and monoammonium phosphate, MAP) at two rates (Pb:P molar ratio 1:4 and 1:6) and incubated for up to 24 weeks. Bioaccessible Pb concentrations were periodically measured using a modified physiologically based extraction test. Fractionation and speciation of Pb were determined through sequential chemical extraction and synchrotron techniques, including X-ray absorption spectroscopy (XAS) and spatially-resolved micro X-ray diffraction (µ-XRD) and µ-XAS, aided by micro X-ray fluorescence (µ-XRF), after 24 weeks. Results demonstrated a significant reduction in bioaccessible Pb levels and pH over time in EP4 soil treated with biosolids, compared to untreated soil, with biosolids showing the most pronounced reduction in bioaccessible Pb. Biosolids treatment consistently reduced the bioaccessible Pb fraction in soils from residential areas (EP1, EP2 and EP3). Sequential extraction and synchrotron analysis confirmed the formation of Pb-associated P and Fe minerals, including pyromorphite and Fe (hydro)oxides sorbed Pb. Class A Fe-rich biosolids were most effective in reducing bioaccessible Pb and transforming Pb into residual fractions across all soils (EP1, EP2, EP3, and EP4), regardless of the type of soil and total Pb concentration. The reduced bioaccessible Pb was primarily associated with pyromorphite, Fe (hydro)oxides sorbed Pb, and Pb bound to organic complexes. Overall, applications of biosolids, TSP, and MAP were effective in diminishing exchangeable Pb fractions and forming stable fractions in alkaline soil. Third study addressed limitations associated with standardized dust wipes in measuring important lead parameters such as bioaccessible Pb in household dust samples. To address these limitations, two types of simulated household dust samples (Pb-soil contaminated and Pb-paint contaminated) were created and compared using a standard dust wipe method and a modified micro vacuum method. Results indicated no significant difference between methods in higher Pb concentration dust mixtures (1200 and 1000 mg kg⁻¹); however, in lower Pb concentration dust mixtures (800 to 400 mg kg⁻¹), the dust wipe method yielded significantly higher lead loading. This difference may be attributed to the dust-transferring procedure in the micro vacuum method. Bland and Altman plots indicated good agreement between dust wipe and micro vacuum methods, suggesting potential for developing a standardized micro vacuum method that is low-cost, efficient, and suitable for detailed dust analysis. Furthermore, the fourth study compared two in vitro methods for estimating the proportion of bioaccessible Pb in dust collected by dust wipes: the US-EPA's in-vitro bioaccessible assay (IVBA) method at two pH values (1.5 and 2.5) and the physiologically based extraction test (PBET) at pH 2.5. Results showed significant differences in estimated bioaccessible Pb levels between extraction methods, with PBET demonstrating greater discrimination, particularly in lead-paint contaminated dust. In conclusion, this thesis work provides valuable insights into the efficacy of organic and inorganic soil amendments in reducing bioaccessible Pb concentrations and altering Pb speciation in alkaline soils. Additionally, it proposes improvements in dust collection methods for more accurate Pb analysis in household dust samples, highlighting the importance of selecting appropriate extraction methods for assessing bioaccessible Pb in environmental samples.
Keywords: Lead bioaccessibility; Alkaline soil; Contaminated dust; Residential soil lead contamination; Biosolids; Soil amendments